Electronic-grade perfluorohexyl sulfonic acid for photoresist top anti-reflection film and preparation method of electronic-grade perfluorohexyl sulfonic acid

Perfluorohexylsulfonic acid is purified by dilution and ion exchange, and the bipolar film and male film structure in the electrolytic cell is used to electrolyze the problem of low imaging accuracy of the photoresist and difficult to control the impurities of perfluorohexylsulfonic acid, which is achieved with high purity and low cost electronic grade perfluorohexylsulfonic acid preparation, suitable for the top anti-reflective film of photoresist.

CN119912368APending Publication Date: 2025-05-02GANSU RUISIKE NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510100698.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

In the existing lithography technology, the dimensional accuracy of photoresist imaging is low, and the composition used to form the top antireflective film has insufficient processability, film formation, refractive index, coating amount or raw material cost, and the impurity metal ions and particle count in perfluorohexylsulfonic acid are difficult to meet the strict requirements of the semiconductor industry.

Method used

A simple and low-cost electronic-grade perfluorohexylsulfonic acid is used to prepare electronic-grade perfluorohexylsulfonic acid, dilute perfluorohexylsulfonic acid and hydrofluoroic acid, purify using an ion exchange column, and electrolytes through the bipolar film and the male film structure in the electrolytic cell, and controls the electrolytic conditions to achieve the purity of metal ion at level E3.

Benefits of technology

Electronic grade perfluorohexylsulfonic acid for photoresist top antireflection film with impurity ions meeting the E3 standard is achieved. It is simple to operate, low energy consumption, low cost and high safety factor. It is suitable for the preparation of photoresist top antireflection film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005254113470000101
    Figure BDA0005254113470000101
  • Figure BDA0005254113470000102
    Figure BDA0005254113470000102
  • Figure BDA0005254113470000111
    Figure BDA0005254113470000111
Patent Text Reader

Abstract

The invention discloses electronic-grade perfluorohexyl sulfonic acid for an anti-reflection film on the top of photoresist and a preparation method of the electronic-grade perfluorohexyl sulfonic acid. The applicant prepares the electronic-grade perfluorohexyl sulfonic acid by using a high-purity inert anode plate in an electrolytic impurity removal mode in an early-stage experimental process, and removes impurities by adding electrolytically purified resin into an anode chamber; in the prior art, the perfluorohexyl sulfonic acid reaches the E3 standard, but the conditions of the method are strict, the E3-grade perfluorohexyl sulfonic acid can be generated only by purifying the resin until the resin contains a very small amount of foreign ions, the process is complex, and the cost is high. On the basis, low voltage and low current are adopted for operation, impurity metal ions separated out from the anode plate are prevented from entering the perfluorohexyl sulfonic acid by utilizing the bipolar membrane, and then the impurity ions in the perfluorohexyl sulfonic acid in the middle chamber are migrated to the cathode chamber by utilizing the electric acting force; the problem that impurity metal ions continuously separated out by the anode plate enter sulfonic acid is essentially solved, the operation method is simpler, the energy consumption is low, the cost is low, and the safety coefficient is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photolithography, in particular to electronic-grade perfluorohexyl sulfonic acid for an anti-reflective film on the top of a photoresist. The invention also relates to a preparation method of the electronic-grade perfluorohexyl sulfonic acid. Background Art

[0002] Photolithography technology is a method of transferring the semiconductor circuit pattern on a photomask to a silicon wafer. The pattern transfer process is completed by irradiating the photomask template with a laser or electron beam, causing the photosensitive material on the wafer to change its material properties due to light exposure.

[0003] The existing photolithography technology has the technical problem of light scattering, which leads to low dimensional accuracy of photoresist imaging. The current mainstream solution is to add a top anti-reflection film formed by a fluorine-containing compound with low refractive index and high transmittance before and after photoresist coating to reduce the interference of light in the photoresist and prevent the change of photolithography line width due to the change of photoresist thickness. The composition used to form the top anti-reflection film for photolithography in the prior art still has certain deficiencies in processability, film forming property, refractive index, coating amount or raw material cost.

[0004] Based on the above, patent CN114035405B discloses a composition for preparing a top anti-reflection film for photoresist, a top anti-reflection film for photoresist and a fluorine-containing composition, which indicates that the part of the photoresist irradiated by a specific light source undergoes a photochemical reaction to produce H + When the pH value of the top anti-reflection layer is high, the generated hydrogen ions diffuse into the anti-reflection layer, the hydrogen ions in the photoresist area are reduced, and the development is incomplete. The developer cannot be fully removed during the development process, thus forming a T-shaped top, which leads to light scattering and standing wave effects during the photolithography process. Adding an appropriate amount of acid to the top anti-reflection layer system can inhibit the H in the photoresist. + The acid diffuses toward the anti-reflection film to avoid the formation of a T-shaped top. Based on the total weight of the composition for preparing the top anti-reflection film, the amount of the acid added is usually preferably 0.5-3wt%, the composition has good stability and film-forming properties, and can be coated with a smaller amount to form an anti-reflection film with equivalent performance to the anti-reflection film in the prior art. The anti-reflection film has a refractive index of 1.41-1.44 at 248nm, which can effectively reduce the refractive index under 248nm wavelength laser irradiation and can be used as a top anti-reflection film for photoresist.

[0005] The above patent first mentioned that adding an appropriate amount of acid to the top anti-reflective layer system can inhibit the H +Diffusion to the anti-reflection film avoids the formation of T-top. Among them, perfluorohexyl sulfonic acid (Example 6) is selected as the acid pH regulator, and the content of perfluorohexyl sulfonic acid is generally preferably 0.5wt%-3wt%. However, perfluorohexyl sulfonic acid that can be used in the semiconductor industry has strict requirements for the impurity metal ions and the number of particles therein. There are few existing data on perfluorohexyl sulfonic acid, which is almost a blank field. The impurity metal ion content and particle number in the perfluorohexyl sulfonic acid generally available are quite high, and cannot be used for compounding the anti-reflection film on the top of the photoresist. Therefore, purifying perfluorohexyl sulfonic acid and reducing the metal ion content and particle number therein, and reducing the total amount of metal impurity ions to the requirements of customers, is of great significance for improving the added value of perfluorosulfonic acid, and is also of great significance for solving the technical problems of the neck in photoresist materials. In GB / T41881-2022, the electronic grade sulfuric acid standards are divided into five standards: E1, E2, E3, E4, and E5. The customer requires the applicant to control the metal ions in the perfluorosulfonic acid to the metal ion requirements of the four levels of electronic grade sulfuric acid, E1, E2, E3, and E4. The metal ions are controlled between the E4-E1 range, preferably to the E1 level. The higher the level, the higher the added value. Therefore, it is of great technical and economic significance to control the metal ions in perfluorohexane sulfonic acid at a high level for compounding the top anti-reflection film.

[0006] In the early experimental process, the applicant used high-purity inert anode plates to prepare electronic-grade perfluorohexane sulfonic acid by electrolytic decontamination. However, when the high-purity inert anode plates were powered on, impurity ions such as calcium ions and sodium ions would be continuously precipitated. These impurity ions entered the perfluorohexane sulfonic acid, making the obtained product only reach the E4 level. A slight error would cause the impurity ions such as calcium ions and sodium ions in the product to fail to meet the standards, and the product rework rate was high. In order to solve this technical problem, the applicant added electrolytically purified resin to the anode chamber for impurity removal. However, although the perfluorohexane sulfonic acid obtained by this method can meet the E3 standard, it is necessary to add the resin electrolytic purification operation, which makes the method more complicated and the processing cost is also higher. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing electronic-grade perfluorohexane sulfonic acid with a simple process and low cost, so that the impurity ions in the obtained electronic-grade perfluorohexane sulfonic acid can meet the E3 standard and can be used for an anti-reflective film on the top of a photoresist.

[0008] To achieve its purpose, the present invention adopts the following technical solution:

[0009] A method for preparing electronic-grade perfluorohexyl sulfonic acid for an anti-reflective film on a photoresist top comprises the following steps:

[0010] (1) diluting perfluorohexane sulfonic acid with electronic grade pure water to a mass fraction of 1.5-3%;

[0011] (2) diluting electronic grade hydrofluoric acid with electronic grade pure water to a mass fraction of 3-6%;

[0012] (3) taking a hydrogen-type cationic resin and loading it into an ion exchange column, washing it in a countercurrent manner with the electronic-grade hydrofluoric acid diluted in step (2), and then washing it in a downstream manner with electronic-grade pure water until the pH of the washing water is 6-7; purifying the perfluorohexane sulfonic acid diluted in step (1) using the washed ion exchange resin to obtain primary purified perfluorohexane sulfonic acid, wherein the metal ions and their contents are as shown in the following table, in ppb;

[0013] Al Ba Ca Cd Co Cr Cu Fe K Mg Mn Na Zn Ni ≤6 ≤4 ≤9 ≤1 ≤3 ≤4 ≤2 ≤4 ≤10 ≤6 ≤4 ≤200 ≤5 ≤7

[0014] (4) taking E1 electronic grade sulfuric acid and diluting it with electronic grade pure water to a mass fraction of 3-5%; setting a bipolar membrane and a cation membrane between the cathode plate and the anode plate of the electrolytic cell to form an intermediate chamber, and then washing the electrolytic cell and its components with electronic grade pure water until the content of all metal ions in the washing water is less than 1 ppb;

[0015] (5) placing the primary purified perfluorohexane sulfonic acid obtained in step (3) into the middle chamber, loading the anode chamber with diluted electronic grade sulfuric acid, loading the cathode chamber with electronic grade pure water for primary electrolysis, adjusting the electrolysis voltage to 20-30 V, dripping diluted electronic grade sulfuric acid into the cathode chamber until the electrolysis current is 2-3 A, raising the temperature of each anode chamber to 40-70° C., and electrolyzing for 1-1.2 h; after the primary electrolysis is completed, taking out all the cathode chamber solution, adding electronic grade pure water to wash until the metal ions in the washing water are less than 1 ppb, and then adding electronic grade pure water for secondary electrolysis;

[0016] The secondary electrolysis is to adjust the electrolysis voltage to 30-40V, add diluted electronic grade sulfuric acid to the cathode chamber until the electrolysis current is 3-4A, raise the temperature of each chamber to 40-70°C, and perform electrolysis for 1-1.2h; after the secondary electrolysis, take out all the cathode chamber solution, add electronic grade pure water to wash until the metal ions in the washing water are less than 1ppb, and then add electronic grade pure water to perform the third electrolysis;

[0017] The electrolysis voltage is adjusted to 40-50V for three electrolysis, diluted electronic grade sulfuric acid is added to the cathode chamber until the electrolysis current is 4-5A, the temperature of each chamber is raised to 40-70°C, and the electrolysis is performed for 1-1.2h; after the three electrolysis, all the cathode chamber solution is taken out, and electronic grade pure water is added to wash until the metal ions in the washing water are less than 1ppb, and then electronic grade pure water is added to perform the fourth electrolysis;

[0018] Adjust the electrolysis voltage to 25-30V for the fourth electrolysis, add diluted electronic grade sulfuric acid to the cathode chamber until the electrolysis current is 2-2.5A, raise the temperature of each chamber to 40-70°C, and perform electrolysis for 1h-1.2h; after the fourth electrolysis, take out all the cathode chamber solution, add electronic grade pure water to wash until the metal ions in the washing water are less than 1ppb, and then add electronic grade pure water to perform the fifth electrolysis;

[0019] Adjust the electrolysis voltage to 30-35V for five electrolysis, add diluted electronic grade sulfuric acid to the cathode chamber until the electrolysis current is 2.5-3A, raise the temperature of each cathode chamber to 40-70℃, and electrolyze for 1h-1.2h. At this point, the electrolysis is finished;

[0020] (6) After the step (5) is electrolyzed continuously for 5 times, the post-electrolysis liquid in the middle chamber is taken out and sampled for testing the metal ions therein; then, filter elements of 0.05 μm, 0.02 μm, 0.01 μm, and 0.01 μm are connected in series, firstly, electronic grade pure water is used for dynamic circulation washing for 24-48 hours, and then the number of particles in the water is tested. When the number of 0.5 μm particles in the water is less than 10 ea / ml, the number of 0.3 μm particles is less than 50 ea / ml, and the number of 0.2 μm particles is less than 100 ea / ml, the post-electrolysis liquid is dynamically circulated and filtered to obtain electronic grade perfluorohexane sulfonic acid.

[0021] As a further preferred embodiment of the technical solution of the present invention, in step (3), the ion exchange column is three hydrogen-type cationic resin exchange columns connected in series.

[0022] Furthermore, in step (3), the ion exchange column is first washed countercurrently with diluted electronic grade hydrofluoric acid twice, each time for more than 24 hours, and then washed downstream with electronic grade pure water until the pH of the washing water is 6-7.

[0023] Furthermore, in step (3), the diluted perfluorohexane sulfonic acid is purified twice continuously using an ion exchange column.

[0024] Furthermore, in step (6), the liquid after electrolysis is dynamically circulated and filtered for 24-48 hours.

[0025] The single metal ions of the electronic-grade perfluorohexyl sulfonic acid prepared by the preparation method are all less than 1 ppb, and can be used as an acid regulator in the preparation of an anti-reflective film on the top of a photoresist.

[0026] By adopting the above technical solution, the beneficial effects of the present invention are:

[0027] (1) The present invention is simple to operate and is operated at low voltage and low current to obtain electronic grade perfluorohexyl sulfonic acid for anti-reflective film on top of photoresist, with impurity ions reaching E3 standard, low energy consumption, low cost and high safety factor.

[0028] (2) In the early experimental process, the applicant used a high-purity inert anode plate to prepare electronic-grade perfluorohexyl sulfonic acid by electrolytic decontamination. In order to solve the technical problem that the high-purity inert anode plate will continuously precipitate impurity ions such as calcium and sodium when it is energized, so that the obtained product cannot meet the higher-level requirements of customers, the applicant added electrolytically purified resin into the anode chamber to remove impurities so that the obtained perfluorohexyl sulfonic acid meets the E3 standard. However, this method has strict conditions and requires the resin to be purified to contain a very small amount of impurity ions to generate E3-level perfluorohexyl sulfonic acid. The process is complicated and the cost is high. The present invention uses a bipolar membrane to prevent the impurity metal ions precipitated from the anode plate from entering the perfluorohexyl sulfonic acid, and then uses electrical force to migrate the impurity ions in the perfluorohexyl sulfonic acid in the middle chamber to the cathode chamber, which essentially solves the problem of the anode plate continuously precipitating impurity metal ions into the sulfonic acid, and the operation method is simpler.

[0029] (3) In the early stage of the applicant's preparation of electronic-grade perfluorohexane sulfonic acid by electrolytic decontamination using high-purity inert anode plates, since the cathode and cathode chambers were all filled with perfluorohexane sulfonic acid, and perfluorohexane sulfonic acid was a surfactant, during the electrolytic decontamination process, the cathode and cathode continuously produced gas. When the liquid level in the cathode and cathode chambers was high, if the temperature was not properly controlled, the overflowing perfluorohexane sulfonic acid would not only affect the circuit safety, but also react with the electrode clamps after contact, causing the product liquid to turn green, seriously affecting the decontamination effect and causing secondary heavy metal ion pollution. To solve the above problems, the present invention places the easily foaming surfactant perfluorohexane sulfonic acid in the middle chamber while controlling the temperature, without contacting the cathode and cathode plates, and only with ion migration. The cathode and cathode chambers are replaced with non-surfactant electronic-grade sulfuric acid that is not easy to foam, respectively, solving the problems of bubbling and secondary metal pollution in decontamination. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a diagram showing the arrangement of the electrolytic cell, cation membrane and bipolar membrane used in the preparation method of the present invention. DETAILED DESCRIPTION

[0031] The preparation method of electronic grade perfluorohexane sulfonic acid for the anti-reflective film on the top of the photoresist of the present invention is described in detail below with reference to specific embodiments.

[0032] In the following examples, all operations are performed in a Class 100 clean room, and electronic grade pure water is electronic water with metal ions less than 1 ppb. In the electrolytic cell, the anode plate is a high-purity platinum plate, and the cathode plate is a high-purity graphite plate.

[0033] Electronic grade hydrofluoric acid was purchased from Duofuduo Chemical Co., Ltd. After dilution, the content of individual metal ions in the electronic grade hydrofluoric acid was less than 1 ppb.

[0034] The perfluorohexane sulfonic acid in step (1) was purchased from Shanghai Jizhi Biochemical Co., Ltd. The full element analysis results are shown in Table 1.

[0035] Table 1 All element analysis results of commercially available perfluorohexane sulfonic acid (unit: ppb)

[0036] Al Ba Ca Cd Co Cr Cu Fe K Mg Mn Na Zn Ni 319 56 3493 0 0 211 607 734 1500 348 6.3 1659 0 12

[0037] Example 1

[0038] (1) diluting perfluorohexane sulfonic acid with electronic grade pure water to a mass fraction of 2%;

[0039] (2) diluting electronic grade hydrofluoric acid with electronic grade pure water to a mass fraction of 5%;

[0040] (3) The hydrogen-type cationic resin is loaded into an ion exchange column, and the diluted electronic-grade hydrofluoric acid in step (2) is used for countercurrent washing for 24 hours, and then the washed water is washed downstream with electronic-grade pure water until the pH of the washed water is 6; the perfluorohexane sulfonic acid diluted in step (1) is purified using the washed ion exchange resin to obtain primary purified perfluorohexane sulfonic acid, wherein the metal ions and their contents are shown in Table 2.

[0041] Table 2 Full element analysis results of primary purified perfluorohexane sulfonic acid (unit: ppb)

[0042] Al Ba Ca Cd Co Cr Cu Fe K Mg Mn Na Zn Ni 5 3 9 1 3 4 2 4 6 5 4 196 5 1

[0043] (4) taking E1 electronic grade sulfuric acid and diluting it with electronic grade pure water to a mass fraction of 3%; setting a bipolar membrane and a cation membrane between the cathode plate and the anode plate of the electrolytic cell to form an intermediate chamber, and then washing the electrolytic cell and its components with electronic grade pure water until the content of all metal ions in the washing water is less than 1 ppb;

[0044] (5) placing the primary purified perfluorohexane sulfonic acid obtained in step (3) into the middle chamber, loading the anode chamber with diluted electronic grade sulfuric acid, loading the cathode chamber with electronic grade pure water for primary electrolysis, adjusting the electrolysis voltage to 20 V, dripping diluted electronic grade sulfuric acid into the cathode chamber until the electrolysis current is 2 A, raising the temperature of each anode chamber to 60° C., and electrolyzing for 1 hour; after the primary electrolysis is completed, taking out all the cathode chamber solution, adding electronic grade pure water to wash until the metal ions in the washing water are less than 1 ppb, and then adding electronic grade pure water for secondary electrolysis;

[0045] In the secondary electrolysis, the electrolysis voltage was adjusted to 30V, diluted electronic grade sulfuric acid was added to the cathode chamber until the electrolysis current was 3A, the temperature of each chamber was raised to 60°C, and the electrolysis was performed for 1 hour; after the secondary electrolysis, all the cathode chamber solution was taken out, and electronic grade pure water was added to wash until the metal ions in the washing water were less than 1ppb, and then electronic grade pure water was added to perform the third electrolysis;

[0046] The electrolysis voltage was adjusted to 40V for three electrolysis, and diluted electronic grade sulfuric acid was added to the cathode chamber until the electrolysis current was 4A. The temperature of each chamber was raised to 60°C and electrolysis was performed for 1 hour. After the three electrolysis, all the cathode chamber solutions were taken out, and electronic grade pure water was added to wash until the metal ions in the washing water were less than 1ppb, and then electronic grade pure water was added to perform the fourth electrolysis.

[0047] The electrolysis voltage was adjusted to 25V for the fourth electrolysis, and diluted electronic grade sulfuric acid was added to the cathode chamber until the electrolysis current was 2A. The temperature of each chamber was raised to 60°C and the electrolysis was performed for 1 hour. After the fourth electrolysis, all the cathode chamber solution was taken out, and electronic grade pure water was added to wash until the metal ions in the washing water were less than 1ppb, and then electronic grade pure water was added to perform the fifth electrolysis.

[0048] The electrolysis voltage was adjusted to 30 V for five electrolysis, and diluted electronic grade sulfuric acid was added to the cathode chamber until the electrolysis current was 2.5 A. The temperature of each cathode chamber was raised to 60 ° C, and the electrolysis was performed for 1 hour. At this point, the electrolysis was terminated;

[0049] (6) After the step (5) is completed with 5 consecutive electrolysis, the post-electrolysis liquid in the middle chamber is taken and sampled for testing the metal ions therein; then, filter elements of 0.05 μm, 0.02 μm, 0.01 μm, and 0.01 μm are connected in series, firstly washed with electronic grade pure water in a dynamic circulation for 24 hours, and then the number of particles in the water is tested. When the number of 0.5 μm particles in the water is less than 10 ea / ml, the number of 0.3 μm particles is less than 50 ea / ml, and the number of 0.2 μm particles is less than 100 ea / ml, the post-electrolysis liquid is dynamically circulated and filtered for 24 hours to obtain electronic grade perfluorohexane sulfonic acid. The number of 0.5 μm particles in the electronic grade perfluorohexane sulfonic acid is 7 ea / ml, the number of 0.3 μm particles is 48 ea / ml, and the number of 0.2 μm particles is 88 ea / ml.

[0050] Table 3 Full element analysis results of electronic grade perfluorohexane sulfonic acid in Example 1 (unit: ppb)

[0051] Al Ba Ca Cd Co Cr Cu Fe K Mg Mn Na Zn Ni Product 0.3 0.2 0.4 0.1 0.2 0.3 0.1 0.2 0.3 0.2 0.1 0.5 0.2 0.1

[0052] Example 2-Example 10

[0053] The other steps of Example 2-10 are the same as those of Example 1, except that the mass fraction of the diluted perfluorohexane sulfonic acid in step (1) is changed. The results of the single metal ion content in the final electronic grade perfluorohexane sulfonic acid product are shown in Table 4.

[0054] Table 4 Single metal ion content in electronic grade perfluorohexane sulfonic acid products in Examples 2-10

[0055]

[0056] From the above examples, it can be seen that when the mass fraction of the perfluorohexane sulfonic acid after dilution in step (1) is 1.5-3%, the content of single metal ions in the obtained perfluorohexane sulfonic acid can reach the E3 level, and the effect is good. Therefore, the mass fraction of the perfluorohexane sulfonic acid after dilution is preferably selected to be 1.5%-3%.

[0057] Examples 13-20

[0058] Examples 13-20 are the same as Example 1 in other steps, except that the mass fraction of the electronic-grade hydrofluoric acid after dilution in step (2) is changed. The results of the single metal ion content in the final electronic-grade perfluorohexane sulfonic acid product are shown in Table 5.

[0059] Table 5 Content of individual metal ions in electronic grade perfluorohexane sulfonic acid products in Examples 13-20

[0060]

[0061]

[0062] From the above embodiment, it can be seen that when the mass fraction of electronic-grade hydrofluoric acid after dilution in step (2) is 3-6%, the content of single metal ions in the obtained electronic-grade perfluorohexane sulfonic acid can reach the E3 level, and the effect is good. Considering the use of the least amount of hydrofluoric acid to reduce costs, the mass fraction of electronic-grade hydrofluoric acid after dilution is preferably selected to be 3%.

[0063] Examples 21-26

[0064] Examples 21-26 are the same as Example 1 in other steps, except that the electronic grade sulfuric acid in step (4) is diluted to different mass fractions. The results of the single metal ion content in the final electronic grade perfluorohexane sulfonic acid product are shown in Table 6.

[0065] Table 6 Content of individual metal ions in electronic grade perfluorohexane sulfonic acid products in Examples 21-26

[0066]

[0067] It can be seen from the above embodiments that when the mass fraction of the electronic-grade sulfuric acid after dilution in step (4) is 3%-5%, the content of single metal ions in the obtained electronic-grade perfluorohexane sulfonic acid can reach the E3 level, and the effect is good.

[0068] Embodiment 27-33 Embodiment

[0069] The other steps of Examples 27-33 are the same as those of Example 1, except that the number of continuous electrolysis in step (4) is changed. When the number of continuous electrolysis is other values, whether the total metal ions in the final product can reach the E3 standard is shown in Table 7.

[0070] Table 7 Content of individual metal ions in electronic grade perfluorohexane sulfonic acid products in Examples 27-33

[0071]

[0072] From the above examples, it can be seen that when the number of continuous electrolysis in step (2) is 5-8 times, the metal ions in the obtained perfluorohexane sulfonic acid can reach the E3 standard. Therefore, the number of continuous electrolysis is preferably selected to be 5 times.

[0073] Example 34-Example 41

[0074] The other steps of Example 34-Example 41 are the same as those of Example 1, except that the electrolysis voltage in step (4) is changed. When the electrolysis voltage is at other values, whether the total metal ions in the final product meet the E3 standard is shown in Table 8.

[0075] Table 8 Content of individual metal ions in electronic grade perfluorohexane sulfonic acid products in Examples 34-41

[0076]

[0077]

[0078] From the above embodiment, it can be seen that when the step (5) 20V≤1 electrolysis voltage≤40V, 30V≤2 electrolysis voltage≤50V, 40V≤3 electrolysis voltage≤60V, 25V≤4 electrolysis voltage≤40V, 30≤5 electrolysis voltage≤45V, the metal ion content in the obtained electronic grade perfluorohexane sulfonic acid reaches E3 level, and the effect is good. Considering the reduction of energy consumption and cost, the electrolysis voltage is preferably selected as 20-30V for the first time, 30-40V for the second time, 40-50V for the third time, 25-30V for the fourth time, and 30-35V for the fifth time.

[0079] Example 42-Example 48

[0080] The other steps of Example 42-Example 48 are the same as those of Example 1, except that the electrolysis current in step (4) is changed. When the electrolysis current is at other values, whether the total metal ions in the final product meet the E3 standard is shown in Table 9.

[0081] Table 9 Content of individual metal ions in electronic grade perfluorohexane sulfonic acid products in Examples 42-48

[0082]

[0083] From the above embodiment, it can be seen that when step (5) 2A≤1 electrolysis current≤4A, 3A≤2 electrolysis current≤5A, 4A≤3 electrolysis current≤6A, 2A≤4 electrolysis current≤3.5A, 2.5A≤5 electrolysis current≤4A, the metal ion content in the obtained electronic grade perfluorohexane sulfonic acid reaches E3 level, and the effect is good. Considering reducing energy consumption and reducing costs, the first electrolysis voltage is preferably 2-3A, the second electrolysis voltage is 3-4A, the third electrolysis voltage is 4-5A, the fourth electrolysis voltage is 2-2.5A, and the fifth electrolysis voltage is 2.5A-3A.

[0084] Example 49-Example 61

[0085] The other steps of Example 49-Example 61 are the same as those of Example 1, except that the electrolysis time in step (4) is changed. When the electrolysis time is at other values, whether the total metal ions in the final product reach the E3 level is shown in Table 10.

[0086] Table 10 Content of individual metal ions in electronic grade perfluorohexane sulfonic acid products of Examples 49-61

[0087]

[0088] From the above embodiment, it can be seen that when the electrolysis time of step (5) is 1h≤1 time≤1.4h, 1h≤2 time≤1.4h, 1h≤3 time≤1.4h, 1h≤4 time≤1.4h, 1h≤5 time≤1.4h, the total metal ion content in the obtained perfluorohexyl sulfonic acid can reach the E3 standard, and the effect is good. Considering the reduction of energy consumption and cost, therefore, the electrolysis time of 1 time is preferably selected to be 1-1.2h, the electrolysis time of 2 times is 1-1.2h, the electrolysis time of 3 times is 1-1.2A, the electrolysis time of 4 times is 1-1.2h, and the electrolysis time of 5 times is 1-1.2h.

[0089] Example 62-Example 72

[0090] The other steps of Example 62-Example 72 are the same as those of Example 1, except that the electrolysis temperature in step (4) is changed. When the electrolysis temperature is at other values, whether the total metal ions in the final product meet the E3 standard shown in Table 11.

[0091] Table 11 Content of individual metal ions in electronic grade perfluorohexane sulfonic acid products in Examples 62-72

[0092]

[0093] From the above examples, it can be seen that when the electrolysis temperature in step (4) is 40°C-70°C, the total metal ions in the obtained perfluorohexane sulfonic acid meet the E3 standard, and the effect is good. Considering the reduction of energy consumption and cost, the electrolysis temperature is preferably selected to be 40°C.

[0094] Comparative Example 1-Comparative Example 3

[0095] Comparative Examples 1 to 3 (Comparative Examples 1 to 3 are parallel experiments) are the same as Example 1 except that no bipolar membrane is provided. When no bipolar membrane is provided, the results of whether the metal ion content in the final electronic grade perfluorohexane sulfonic acid product reaches the E4 or E3 level are shown in Table 12.

[0096] Table 12 Content of single metal ions in electronic grade perfluorohexane sulfonic acid products in comparative examples 1-3

[0097]

[0098] It can be seen from the above Comparative Examples 1 to 3 that when no bipolar membrane is provided, the metal ions in the final product after the electrolysis is completed cannot meet the customer's minimum requirement E4 standard.

[0099] Comparative Example 4-Comparative Example 6

[0100] Comparative Examples 4 to 6 (Comparative Examples 4 to 6 are parallel experiments) are the same as Example 1 except that no cation membrane is provided. When no cation membrane is provided, the results of whether the metal ion content in the final electronic grade perfluorohexane sulfonic acid product reaches the E4 or E3 level are shown in Table 13.

[0101] Table 13 Single metal ion content in electronic grade perfluorohexane sulfonic acid products in comparative examples 1-3

[0102]

[0103] It can be seen from the above Comparative Examples 4 to 6 that when no cation membrane is provided, the metal ions in the final product after the electrolysis is completed cannot meet the customer's minimum requirement E4 standard.

Claims

1. A method for preparing electronic grade perfluorohexane sulfonic acid for anti-reflective film on top of photoresist, characterized in that: The following steps are involved: (1) diluting perfluorohexane sulfonic acid with electronic grade pure water to a mass fraction of 1.5-3%; (2) diluting electronic grade hydrofluoric acid with electronic grade pure water to a mass fraction of 3-6%; (3) taking a hydrogen-type cationic resin and loading it into an ion exchange column, washing it in a countercurrent manner with the electronic-grade hydrofluoric acid diluted in step (2), and then washing it in a downstream manner with electronic-grade pure water until the pH of the washing water is 6-7; purifying the perfluorohexane sulfonic acid diluted in step (1) using the washed ion exchange resin to obtain primary purified perfluorohexane sulfonic acid, wherein the metal ions and their contents are as shown in the following table, in ppb; (4) taking E1 electronic grade sulfuric acid and diluting it with electronic grade pure water to a mass fraction of 3% to 5%; setting a bipolar membrane and a cation membrane between the cathode plate and the anode plate of the electrolytic cell to form an intermediate chamber, and then washing the electrolytic cell and its components with electronic grade pure water until the content of all metal ions in the washing water is less than 1 ppb; (5) placing the primary purified perfluorohexane sulfonic acid obtained in step (3) into the middle chamber, loading the anode chamber with diluted electronic grade sulfuric acid, loading the cathode chamber with electronic grade pure water for primary electrolysis, adjusting the electrolysis voltage to 20-30 V, dripping diluted electronic grade sulfuric acid into the cathode chamber until the electrolysis current is 2-3 A, raising the temperature of each anode chamber to 40-70° C., and electrolyzing for 1-1.2 h; after the primary electrolysis is completed, taking out all the cathode chamber solution, adding electronic grade pure water to wash until the metal ions in the washing water are less than 1 ppb, and then adding electronic grade pure water for secondary electrolysis; The secondary electrolysis is to adjust the electrolysis voltage to 30-40V, add diluted electronic grade sulfuric acid to the cathode chamber until the electrolysis current is 3-4A, raise the temperature of each chamber to 40-70°C, and perform electrolysis for 1-1.2h; after the secondary electrolysis, take out all the cathode chamber solution, add electronic grade pure water to wash until the metal ions in the washing water are less than 1ppb, and then add electronic grade pure water to perform the third electrolysis; The electrolysis voltage is adjusted to 40-50V for three electrolysis, diluted electronic grade sulfuric acid is added to the cathode chamber until the electrolysis current is 4-5A, the temperature of each chamber is raised to 40-70°C, and the electrolysis is performed for 1h-1.2h; after the three electrolysis, all the cathode chamber solution is taken out, and electronic grade pure water is added to wash until the metal ions in the washing water are less than 1ppb, and then electronic grade pure water is added to perform the fourth electrolysis; Adjust the electrolysis voltage to 25-30V for the fourth electrolysis, add diluted electronic grade sulfuric acid to the cathode chamber until the electrolysis current is 2-2.5A, raise the temperature of each chamber to 40-70°C, and perform electrolysis for 1h-1.2h; after the fourth electrolysis, take out all the cathode chamber solution, add electronic grade pure water to wash until the metal ions in the washing water are less than 1ppb, and then add electronic grade pure water to perform the fifth electrolysis; Adjust the electrolysis voltage to 30-35V for five electrolysis, add diluted electronic grade sulfuric acid to the cathode chamber until the electrolysis current is 2.5-3A, raise the temperature of each cathode chamber to 40-70℃, and electrolyze for 1h-1.2h. At this point, the electrolysis is finished; (6) After the step (5) is electrolyzed continuously for 5 times, the post-electrolysis liquid in the middle chamber is taken out and sampled for testing the metal ions therein; then, filter elements of 0.05 μm, 0.02 μm, 0.01 μm, and 0.01 μm are connected in series, firstly, electronic grade pure water is used for dynamic circulation washing for 24 h to 48 h, and then the number of particles in the water is tested. When the number of 0.5 μm particles in the water is less than 10 ea / ml, the number of 0.3 μm particles is less than 50 ea / ml, and the number of 0.2 μm particles is less than 100 ea / ml, the post-electrolysis liquid is dynamically circulated and filtered to obtain electronic grade perfluorohexane sulfonic acid.

2. The method for preparing electronic grade perfluorohexane sulfonic acid for photoresist top anti-reflection film according to claim 1, characterized in that: In step (3), the ion exchange column is three hydrogen-type cationic resin exchange columns connected in series.

3. The method for preparing electronic grade perfluorohexane sulfonic acid for photoresist top anti-reflection film according to claim 2, characterized in that: In step (3), the ion exchange column is first washed countercurrently twice with diluted electronic grade hydrofluoric acid, each time for more than 24 hours, and then washed downstream with electronic grade pure water until the pH of the washing water is 6-7.

4. The method for preparing electronic grade perfluorohexane sulfonic acid for photoresist top anti-reflection film according to claim 3, characterized in that: In step (3), the diluted perfluorohexane sulfonic acid is purified twice continuously using an ion exchange column.

5. The method for preparing electronic grade perfluorohexane sulfonic acid for photoresist top anti-reflection film according to claim 3, characterized in that: In step (6), the liquid after electrolysis is dynamically circulated and filtered for 24-48 hours.

6. Electronic-grade perfluorohexyl sulfonic acid prepared by the method for preparing electronic-grade perfluorohexyl sulfonic acid for anti-reflective film on top of photoresist as claimed in any one of claims 1 to 5.